2016
DOI: 10.4081/monaldi.2007.506
|View full text |Cite
|
Sign up to set email alerts
|

Indications for flexible fiberoptic bronchoscopy and its safety in the very elderly

Abstract: Aim. To evaluate the indications and the safety of fiberoptic bronchoscopy (FOB) with bronchoalveolar lavage (BAL), protected specimen brushing (PSB), endobronchial biopsy (EBB), and transbronchial biopsy (TBB) in a population of very elderly patients. Methods. We performed a retrospective study of all adult patients, aged 50 years or older, who underwent FOB in the Bronchology Unit of the University of Parma Hospital between 1 January, 2003 and 31 April, 2005. Bronchoscopy records of 436 consecutive patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…Six prospective studies (57, 58, 64–66, 72) and two retrospective studies (55, 73) listed pneumothorax as a potential outcome, with rates ranging from 0 to 4% (58, 72). Two studies reported no pneumothoraces in various bioptic techniques that included TBB (66, 72).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six prospective studies (57, 58, 64–66, 72) and two retrospective studies (55, 73) listed pneumothorax as a potential outcome, with rates ranging from 0 to 4% (58, 72). Two studies reported no pneumothoraces in various bioptic techniques that included TBB (66, 72).…”
Section: Resultsmentioning
confidence: 99%
“…Three prospective studies (57, 74, 75) and one retrospective study with prospective recordings of bronchospasm (55) reported on bronchospasm. Bronchospasm occurred at a rate between 0 and 12.3% (57, 75).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor : Fiberoptic bronchoscopy is thought to be useful for diagnosing abnormalities in the lower respiratory tract and pulmonary parenchyma and is considered to be a safe method of examination, with a low rate of associated complications and mortality in the general population . However, the safety of fiberoptic bronchoscopy in very elderly adults has been evaluated in only a small number of studies and, before the present study, has never been evaluated in a prospective multicenter clinical trial . The aim of this prospective multicenter study was thus to compare the complications of fiberoptic bronchoscopy in very elderly adults with those in younger individuals.…”
Section: Characteristics Of the Study Population And Indications Formentioning
confidence: 94%
“…[ 1 ] Lung cancer was the indication behind its development and still is one of the commonest indications worldwide for flexible bronchoscopy. [ 3 4 5 ] Flexible bronchoscopy has a huge impact on the management of lung cancer. It helps in both diagnosing and staging lung cancer as well as palliation by debulking endobronchial lesions and treating airway stenoses by deploying metallic airway stents.…”
mentioning
confidence: 99%